TLC screening for free radical scavenger and polyphenolic antioxidant in marine algae - Mohd Fauzi, Muhammad Lutfi (2017)
The aim of the study is to quantify the polyphenolic content and free radical scavenging activity in various species of marine algae. Due to presence of antioxidant and free radical scavenger, marine algae can thrive the extreme environmental condition where exposure to extreme light and high concentration of oxygen. Polyphenolic compound which is secondary metabolite of algae has free radical scavenging potential. Phenolic compound can act as reducing agent, hydrogen (H) donor, singlet oxygen (0) quencher that can decrease the formation of reactive oxidative species (ROS). In vivo, ROS might cause harm by damaging cellular components. HPTLC with post-derivatization with DPPH• of FeCl3 can be used as method to analyse the total phenolic content and free radical scavenging capacity. This research show that high correlation (r = 0.68) between polyphenolic content and free radical scavenging activity. This correlation suggest that polyphenolics mostly contribute to free radical scavenging activity.